Broken home: Visualization of adolescent life experiences through surrealism illustrations - Benu, Yosua Laharoy Henysen; Setiaji, Rony Siswo (Universitas Negeri Yogyakarta, 2024)
This study aims to (1) determine the impact of a broken home as an object of surrealist illustration creation; (2) determine the creative process of Wadino Artists as an inspiration for surrealist illustration works; (3) compile the concept of creating illustration works based on the impact of a broken home and Wadino's creative process; and (4) describe the visualisation of the concept of surrealist illustration works. This study uses the art-based research method with the object of the impact of the broken home and the inspiration for Wadino's creative process. The subjects of the study were adolescent victims of broken homes aged 17-21 years and Wadino Artists. Data were collected through interviews, questionnaires, film studies, and literature studies and documented through reflective notes. Data analysis was carried out descriptively and qualitatively, with the validity of the data checked through the triangulation of data resources and theories. The results of the study show that (1) the impact of a broken home, such as conflict, trauma, shame, depression, and hatred, inspires surrealist illustrations; (2) Wadino's creative process explores ideas, concepts, media, and visual forms of surrealism; (3) the concept of the work visualises the impact of broken home in a surrealist style; and (4) the process of creating the work involves developing ideas based on the impact of broken homes and Wadino's inspiration, using pencil media with a surrealist style. The resulting illustration works number four: